Oral Health Care Improvement using Combined Toothpaste with Traditional Medicinal Plants - Ali, Muna Jalal (AENSI Journals, 2016)
The evolution of microbes, including the development of resistant strains and adaptation, depend on diverse members of the microbial population that can thrive in new condition. Therefore, microbes present remarkable abilities to evolve faster than their hosts do. Oral isolates of different patients aged 3 years to 60 years were obtained, purified, and tested against four different commercial medicinal plants extracts for antimicrobial activity. A total of 10 different commercial toothpastes (different brands and prices) were collected, and the combined action of the medicinal plants combination and toothpaste was studied by using disc diffusion method to determine the antimicrobial activity of medicinal plants with toothpaste. We found a higher bacterial population in the age group of 3–40 years than the group of 40–60 years, with approximately 44% and 32%, respectively. The combined action of ethanol medicinal plant extracts (alone) against oral isolates showed a synergistic effect, with 32.20%, for combinations A (Ci/Ca). By contrast, the combined action of medicinal plants with 10 different toothpastes improved the antimicrobial sensitivity by 60% for combinations A. In addition, the effectiveness of toothpaste is not related to the price. The ethanol extract of combinations medicinal plants Ci/Ca with commercial toothpaste showed higher antimicrobial activity against oral isolates than other combination groups and the effectiveness of toothpaste is not related to the price.